Enhancing Brand Awareness Through Visual Branding: A Case Study of Pet&Co - Aginsa, Meidina Puteri; Wulansari, Amilia (Journal Integration of Social Studies and Business Development, 2024)
Effective visual branding is essential for boosting brand awareness in Indonesia's rapidly growing pet care industry. This study investigates the challenges faced by Pet&Co, a new pet supplement brand, in enhancing its social media presence and brand recognition. Despite its innovative product, 'Colla Blend,' Pet&Co struggles with low engagement and brand visibility, particularly on Instagram. Through a comprehensive research approach that includes consumer feedback, expert opinions, and a literature review, the study identifies key factors for improving visual branding: logo design, colour scheme, typography, size, shape, and imagery. Proposed strategies to address these branding issues involve enhancing social media marketing, expanding the e-commerce presence, collaborating with pet shops and influencers, targeting B2B markets, and investing in product innovation. These strategies aim to rectify current branding deficiencies and strengthen Pet&Co's market presence. The findings suggest that a multi-platform exposure strategy, combined with dynamic and engaging content, will significantly improve brand visibility and consumer interaction in the competitive pet care industry.